ELEKTRON TÁLIM RESURSLARÍNÍŃ STATUS KOEFFICIENTIN ISLEP ShÍǴIW METODIKASÍNDA INFORMACIYALÍQ TEXNOLOGIYALARDÍŃ ORNÍ HÁM ÁHMIYETI - Baymurzaeva, A.A. (SCIENCE and SOCIETY, 2025)
The article analyzes the role and importance of information technology in the methodology for developing the weighting coefficient of electronic educational resources. The weighting coefficient is considered as an indicator developed to assess the quality, influence and position of electronic educational resources among users. The methods for calculating the weighting coefficient based on information technology are considered, including data analysis, machine learning and processing user feedback.